UNPUZZLING INDIA’S OPEN DEFECATION PUZZLE: A BOXJENKINS ARIMA APPROACH - DR. SMARTSON. P. NYONI; MR. THABANI NYONI (International Journal of Innovations in Engineering Research and Technology, 2021)
A toilet is a life-saver and a dignity-protector not just a toilet! Unfortunately, WHO & UNICEF (2015) imply that the opposite is true for approximately 61% of rural and 10% of urban Indians. In fact, Coffey et al. (2014) note that most people who live in India defecate in the open and that open defecation is far more common in rural India than in urban India. Given that 70% of the total population in India lives in rural areas, it leaves a lot to be desired, especially from a public health perspective. Using annual time series data on the number of people who practice open defecation in India from 2000 – 2017, the study predicts the annual number of people who will still be practicing open defecation over the period 2018 – 2022. The study applies the Box-Jenkins ARIMA approach. The diagnostic ADF tests show that the series under consideration is an I (1) variable. Based on the AIC, the study presents the ARIMA (2, 1, 0) model as the optimal model. The diagnostic tests further reveal that the presented model is stable and its residuals are stationary in levels. The results of the study indicate that the number of people practicing open defecation in India is likely to decline over the period 2018 – 2022, from as high as 23% to as low as 11.8% of the total population. In order to sustain this desirable downwards trend, the study suggested a five-fold policy recommendation to be put into consideration, especially by the Indian government.